GeoGebra software in the improvement of solving capacities of problems of two-dimensional geometric figures in university students - Aldazabal Melgar, Omar Franco (2021)
The objective was to evaluate the effect of the application of the GeoGebra software on the problem-solving skills of two-dimensional geometric figures in a sample of 53 university students distributed in two groups (control -experimental) evaluated in two moments: before and after the intervention. . Parametric tests were used to compare independent and related pairs and nonparametric tests were used to compare between classification levels. The results showed that the post-test experimental group was the one that presented the best performance, demonstrating that the use of GeoGebra software improved the solving skills of this type of mathematical problems, promoting collaborative work, social-student integration and improvement of the classroom climate. It is recommended to extend the use of this tool with other applications that help the teaching-learning process.